ECOLOGICAL ETHICS ISSUESS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This article examines the relationship between ecology and ethics. In the development of modern civilization, philosophical analysis of environmental issues has acquired a significant importance, emphasizing its value-regulating and value-orienting functions. The importance of a socio-ethical assessment of the unity, interconnectedness, and dissonance between humans and nature is demonstrated. Environmental ethics currently faces the challenge of achieving overall harmony in human-nature relationships, whether in business, creativity, or science, and directing this toward resolving the environmental crisis. Therefore, considering the value of nature within the framework of moral responsibility is one of the most important tasks of modern society.
Keywords: : nature, philosophy, environmental issues, environmental ethics, morality, moral responsibility